Marker-assisted backcross breeding for heat tolerance in bread wheat (Triticum aestivum L.) - Bellundagi, Amasiddha; Ramya, K. T.; Krishna, Hari; Jain, Neelu; Shashikumara, P.; Singh, Pradeep Kumar; Singh, Gyanendra Pratap; Prabhu, Kumble Vinod (Frontiers in Genetics, 2022)
Changing flowering time for adaptation either naturally or through genetic approaches may combat heat stress damage that occur at reproductive stages in many production environments. HD2733, a popular wheat variety of the eastern plains of India, is largely sensitive to heat stress. Our study aimed at improving heat tolerance of variety HD2733 by transferring QTLs associated with early anthesis linked to Xbarc186 SSR marker and another QTL associated with high kernel weight under heat stress linked to Xgwm190 SSR marker from a tolerant donor, WH730 following marker assisted backcross breeding (MABB). Around 124 simple sequence repeat (SSR) markers distributed evenly across the wheat genome were employed for the background selection. A total of 266 plants were selected in BC1F1 population and seven plants were used to generate BC2F1 population based on phenotypic similarity to the recipient parent as well as presence of foreground markers. Advancement to each subsequent generation was performed on the basis of presence of targeted QTLs, higher recurrent parent genome (RPG) and greater phenotypic similarity to the recurrent parent. 52 plants with both target QTLs, 37 plants with one QTL linked to Xbarc186 and 30 plants with another QTL linked to Xgwm190 marker were selected in BC2F1 for background screening. Further, 39 BC2F3 and 21 BC1F4 families homozygous for the targeted QTLs with 90.9 to 97.9% and 86.8 to 88.3 % RPG recovery respectively, were selected. Evaluation of the best performing 17 BC2F3 and 10 BC1F4 families for various morpho- physiological traits was carried out. Phenotypic evaluation and multi-location trials of the derived lines under late sown conditions led to the selection of three promising lines with early anthesis and higher grain yield. This will also serve as an excellent genetic material for functional genomics and expression studies to understand the molecular mechanisms and pathways underlying the stress tolerance governed by the respective QTLs without the effect of background noise.